2016
DOI: 10.1186/s12879-016-1920-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug susceptibility profiles of pulmonary Mycobacterium tuberculosis isolates from patients in informal urban settlements in Nairobi, Kenya

Abstract: BackgroundAnti-tuberculosis drug resistance is an emerging health problem in Kenya and especially in slums. Slum environments create a conducive environment for the spread of tuberculosis (TB) due to high population density and lack of basic amenities such as decent housing, access to clean water, lack of drainage and basic sanitation. Furthermore, ineffective health services in crowded and poorer populations, poor patient compliance, a large pool of untreated cases, delayed diagnosis and inappropriate treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Increasing resistance towards second line drugs (SLD's) is a major global threat leading to pre-XDR and XDR-TB which has high mortality rates due to limited treatment options and lower rates of treatment success [1,2]. Timely diagnosis and treatment remains an utmost challenge in order to stop circulating XDR-TB strains and further amplification of resistance [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing resistance towards second line drugs (SLD's) is a major global threat leading to pre-XDR and XDR-TB which has high mortality rates due to limited treatment options and lower rates of treatment success [1,2]. Timely diagnosis and treatment remains an utmost challenge in order to stop circulating XDR-TB strains and further amplification of resistance [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…East African countries such as 5 in Ethiopia (Admassu, 2011 [ 23 ], Mekonnen et al, 2015 [ 24 ], Brhane et al, 2017 [ 25 ], Biresaw et al, 2018 [ 26 ], Girum et al, 2018 [ 27 ]), 2 in Kenya (Kerubo et al, 2016 [ 28 ], Huerga et al, 2017 [ 29 ]), 1 in Rwanda (Umubyeyi et al, 2007 [ 30 ]), 3 in Sudan (Eldin et al, 2011. [ 31 ], Sabeel et al, 2017 [ 32 ], Eldirdery et al, 2017 [ 33 ]), 2 in Tanzania (Chonde et al, 2010 [ 34 ], Range et al, 2012 [ 35 ]) and 3 in Uganda (Lukoye et al, 2011 [ 36 ], Lukoye, 2013 [ 3 ], Okethwangu et al, 2019 [ 37 ]) were used in this systematic review and meta-analysis indicated in S2 Table .…”
Section: Resultsmentioning
confidence: 99%
“…Ndung'u PW et al, (30.0%, 2012) [44], Kerubo G et al, (30.0%, 2016) [45] and Yonge SA et al, (48.6%, 2017) [46] in Kenya; and Aung WW et al, (27.7%, 2015) [47] in Myanmar. However, a lower rate of resistance of M. tuberculosis strains in new presumptive pulmonary TB cases was reported in the previous studies by Biadglegne F et al, (6.7%, 2014) [48] in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%